(untitled) (Journal of Enam Medical College, 2017)
Our history began about 4.5 billion years ago when our solar system was formed and earth started to take a shape. We are being blessed with uncountable number of, known and unknown, natural resources. We are dependent on them as such that sometimes we cannot even notice their presence. Besides enormous beneficial impacts, the environment we live in is a huge reservoir of toxic metals. Our health is under constant risk due to increasing chronic exposure of such metals that adversely affect the quality of life of people. The deterioration of human health due to exposure to heavy metals has become a major issue of concern worldwide. Although adverse health effects caused by heavy metals have been known for a long time, exposure to heavy metals continues, and is even increasing in some parts of the world, particularly in developing countries. One such heavy metal with a high toxicity found in the earths crust, associated with zinc, lead and copper ores is cadmium. Exposure to cadmium has long been recognized as a health hazard, both in industry and in general populations with high exposure. The parts of body that are potentially affected from exposures to cadmium mainly involve the kidney, liver, lung, heart and bone. There is also a positive association between cadmium exposure and increased nephrotoxicity in patients with diabetes mellitus. The objective of this paper is to review available information on possible toxicities specially nephrotoxicity of cadmium on human health in general and also in diabetic population. J Enam Med Col 2017; 7(3): 156-161